2016
DOI: 10.1159/000449337
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pretreatment Scoring Incorporating C-reactive Protein to Predict Overall Survival in Advanced Hepatocellular Carcinoma with Sorafenib Treatment

Abstract: Objectives: This study aimed to build a prediction score of prognosis for patients with advanced hepatocellular carcinoma (HCC) after sorafenib treatment. Methods: A total of 165 patients with advanced HCC who were treated with sorafenib were analyzed. Readily available baseline factors were used to establish a scoring system for the prediction of survival. Results: The median survival time (MST) was 14.2 months. The independent prognostic factors were C-reactive protein (CRP) <1.0 mg/dL [hazard ratio (HR) =0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Recently, sorafenib [9,10] , a molecular targeting drug, has also been found to be effective for the treatment of unresectable HCC in patients with good hepatic function (Child-Pugh A, CP-A) [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sorafenib [9,10] , a molecular targeting drug, has also been found to be effective for the treatment of unresectable HCC in patients with good hepatic function (Child-Pugh A, CP-A) [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…The subclassification of stage C patients has been previously attempted using scoring or substaging methods . Yau and colleagues developed a scoring system consisting of 11 variables with different weights, such as tumour size and total bilirubin, to differentiate the prognosis of patients with advanced HCC .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a moderate increase of hsCRP showed to predict recurrence and survival in patients with early-stage HCC [ 27 ]. Further, it has been demonstrated that a novel prognostic scoring system, which includes the CRP level, predict overall survival in late-stage HCC following treatment with Sorafenib [ 28 ]. Shin et al, found that increased serum CRP concentration indicates poor prognosis in patients with HCC [ 29 ].…”
Section: Discussionmentioning
confidence: 99%